German Economy Summer 2024: Recovery gets off to a slow start - Joscha Beckmann; Jens Boysen-Hogrefe; Dominik Groll; Timo Hoffmann; Nils Jannsen; Stefan Kooths; Christian Schröder; Nils Sonnenberg (Kiel Institute for the World Economy (IfW Kiel), 2024)
The German economy is leaving the recession behind. According to leading indicators, GDP will continue to rise following the increase in the first quarter. As the year progresses, real disposable income and exports will stimulate economic activity. In addition, the effects of tighter monetary policy will gradually fade out. However, there are no signs of a strong economic momentum. Despite a moderate upward trend, business and consumer confidence remain at low levels. Moreover, structural impediments - not least demographic change - are increasingly limiting the scope for expansion. All in all, GDP we expect to grow by 0.2 percent in 2024 (spring forecast: 0.1 percent) and by 1.1 percent in 2025 (spring forecast: 1.2 percent). Although inflation has moderated noticeably and will reach 2.2 percent this year and 1.9 percent in 2025, core inflation will remain elevated for the time being. The labor market remains fairly robust, although employment will increase only slightly due to demographic change. The unemployment rate will remain broadly unchanged and will be 5.8 percent in 2025. The budget deficit will decline from 2.4 percent relative to GDP in 2023 to 1.2 percent in 2025. The debt level will remain at around 63 percent relative to GDP.
Keywords: 330